2021
DOI: 10.1186/s12891-021-04408-0
|View full text |Cite
|
Sign up to set email alerts
|

Pressure pain thresholds in individuals with knee pain: a cross-sectional study

Abstract: Background Knee osteoarthritis (KOA), chronic widespread pain (CWP) and overweight/obesity are public health problems that often coincide, and there is a multifactorial and unclear relationship between them. The study aimed to (1) investigate pain sensitivity, assessed by pressure pain thresholds (PPTs), among women and men with knee pain and (2) associations with, respectively, radiographic KOA (rKOA), CWP, and overweight/obesity. Methods Baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Potential mechanisms regarding our metaregression result could include mechanical loading (e.g., increased joint load and altered walking kinematics in individuals with obesity compared with normal‐weight individuals) (80) and/or systemic factors such as metabolically driven inflammation in obesity (81) or pain sensitivity. Recent work has found that in those with knee pain, low pressure pain thresholds are associated with both higher visceral fat area and body fat percentage (82). This may in part explain why those studies with higher BMI (>28 kg/m 2 ) displayed a negative knee loading–pain relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms regarding our metaregression result could include mechanical loading (e.g., increased joint load and altered walking kinematics in individuals with obesity compared with normal‐weight individuals) (80) and/or systemic factors such as metabolically driven inflammation in obesity (81) or pain sensitivity. Recent work has found that in those with knee pain, low pressure pain thresholds are associated with both higher visceral fat area and body fat percentage (82). This may in part explain why those studies with higher BMI (>28 kg/m 2 ) displayed a negative knee loading–pain relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The study was based on an ongoing longitudinal cohort study (the Halland Knee Osteoarthritis cohort study, HALLOA) that included 306 individuals with knee pain in Southwest Sweden, as described in detail elsewhere [ 7 ]. Participants from the HALLOA study who had performed the two-year follow-up after inclusion were eligible for the current study (n = 101).…”
Section: Methodsmentioning
confidence: 99%
“…KOA can cause chronic pain, impaired physical function, diminished quality of life [ 4 ], and affects workability [ 5 ]. Individuals with knee pain also have a higher risk of developing chronic widespread pain (CWP) [ 6 ], and in a previous study the prevalence of CWP was 38% of those with knee pain [ 7 ]. Health is more than the absence of disease; it is a state of physical, mental, and social well-being [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies are needed to further investigate the associations. 64 In a study of baseline data with the aim to refine and assess the validity of an algorithm to detect lying down from raw data of thigh-worn accelerometers, we have found that the refined algorithm can be used to estimate lying time in studies using different accelerometer brands. 47…”
Section: Findings To Datementioning
confidence: 99%
“…In a study aimed to (1) investigate pain sensitivity, assessed by PPTs, among women and men with knee pain and (2) associations with, respectively, radiographic knee OA, CWP and overweight/obesity, we found that modifiable factors, increased VFA and body fat could be associated with increased pain sensitivity among individuals with knee pain. Longitudinal studies are needed to further investigate the associations 64…”
Section: Findings To Datementioning
confidence: 99%